Uji Aktivitas Antibakteri Ekstrak Etanol Daun Rhizophora mucronata terhadap Shigella dysenteriae - NUGRAHA, MUHAMMAD FIKRY; ARDIANA, DIAN; ASAMI RIETTA KUMALA; NITA PRANITASARI (Hang Tuah Medical Journal, 2025)
Shigella dysenteriae is the most common cause of diarrhea in cases of shigellosis. This bacterium can invade the epithelium of the large intestine, ileum, and rectum, causing diarrhea accompanied by blood and mucus. Effective antibiotic therapy for this disease has shown resistance. The mangrove Rhizophora mucronata contains various secondary metabolites that have the potential to be new antibacterial alternatives. This study is an in vitro laboratory study to determine the inhibitory effect of Rhizophora mucronata leaf extract on the growth of Shigella dysenteriae bacteria. The study used the Kirby-Bauer drop diffusion method with Mueller-Hinton Agar medium and a digital caliper to measure the diameter of the inhibition zone. Twenty-four samples were divided into six groups: negative control (bacterial culture treated with distilled water); treatment groups (Kp) (treated with extract concentrations of 25%, 50%, 75%, and 100%); and positive control (treated with ciprofloxacin 5 mcg). Results: The negative control group and all treatment groups had an average inhibition zone of 6.00 mm or no inhibition zone, while the positive control group had an average of 25.845 mm. The Kruskal-Wallis test (p=0.0001) showed significant differences among the tested groups, and the post hoc test (p=0.014) indicated significant differences between the positive control group and all other groups. The leaf extract of Rhizophora mucronata was not found to have inhibitory activity against the growth of Shigella dysenteriae.-